Accuracy of Multi-Detector Computed Tomography, Fluorodeoxyglucose Positron Emission Tomography-CT, and CA 19-9 Levels in Detecting Recurrent Pancreatic Adenocarcinoma - Hamidian Jahromi, Alireza; Sangster, Guillermo; Zibari, Gazi; Martin, Brett; Chu, Quyen; Takalkar, Amol; Shi, Runhua; Shokouh-Amiri, Hosein (JOP. Journal of the Pancreas, 2013)
Context We compared the accuracy of fluorodeoxyglucose positron emission tomography-CT (FDG-PET-CT), multi-detector computed tomography (MDCT) and CA 19-9 levels in detecting pancreatic cancer recurrence in patients with resected CA 19-9 positive pancreatic adenocarcinomas. Methods We retrospectively evaluated 122 patients with pancreatic adenocarcinomas who underwent surgical resection of the tumor between January 2002 and December 2011. Twenty-five patients had MDCT, FDG-PET-CT and CA 19-9 levels performed no less than six weeks post-operation and within 8 weeks of each other for detection of tumor recurrence. Of these, 20 patients had high pre-operative CA 19-9 levels that dropped to a normal level postoperatively which will be the focus of this study. The sensitivity, specificity, positive and negative predictive value (PPV, NPV), and accuracy of MDCT, FDG-PET-CT, and CA 19-9 in detecting recurrence were compared. Results Operations performed included pyloric sparing pancreaticoduodenectomy (n=9), pancreaticoduodenectomy (n=7), distal pancreatectomy (n=3) and total pancreatectomy (n=1). Three patients had no recurrence, but local recurrence and distant metastasis were seen in 8 (40%) and 12 (60%) patients, respectively. In our study, sensitivity, specificity, PPV, NPV and diagnostic effectiveness (accuracy) were: 82%, 100%, 100%, 50%, 85% for MDCT; 82%, 100%, 100%, 50%, 85% for FDG-PET-CT and 94%, 100%, 100%, 75%, 95% for CA 19-9. The difference in recurrence detection accuracy of the tests was not statistically significant. A combination of CA 19-9 with MDCT or FDG-PET-CT was 100% accurate in detecting cancer recurrence in our patients. Conclusion Our data suggests that CA 19-9 levels can be used reliably to detect recurrent pancreatic adenocarcinomas in patients with CA 19-9-positive primary tumors. Combination of CA 19-9 with MDCT or FDG-PET-CT is potentially the most accurate approach in detecting pancreatic cancer recurrence. Image: Surgeons from the patient's wiev (The Willis Knighton Health System "John C. McDonald Regional Transplant Center". Shreveport, LA, USA).